Double Superposed Epoch Analysis of Geomagnetic Storms and Corresponding Solar Wind and IMF in Solar Cycles 23 and 24. Issue 3 (22nd March 2023) - Manu, V.; Balan, N.; Zhang, Qing‐He; Xing, Zan‐Yang
Abstract: The weakest solar cycle 24 (SC24, 2010–2019) in 100 years was 1/3rd less active compared to the previous solar cycle 23 (SC23, 1996–2009). We identify 135 and 61 ICME (interplanetary coronal mass ejection) driven clear geomagnetic storms (DstMin ≤ −50 nT) in SC23 and SC24, respectively, giving a reduction of 55% storms in SC24, and present the double superposed epoch analysis (DSEA) of the storms/activities in SC23 and SC24 using the Dst, symmetric H (SymH), Kp and AE indices. The DSEA method for the corresponding solar wind velocity V, north‐south component of the interplanetary magnetic field (IMF Bz) and the product VBz are also presented. Compared to SC23, the maximum storm/activity intensity in SC24 reduces by 52%, 12%, and 45% at low, mid and high latitudes and the corresponding maxima in ‐VBz, V, and ‐Bz reduce by 39%, 17%, and 38%, respectively. The epoch average storm/activity intensity reduces by 27%, 11%, and 4% at low, mid and high latitudes and average maxima in ‐VBz, V, and ‐Bz reduce by 24%, 14%, and 13%, respectively. The results seem to reveal that the average reduction in the main driver ‐VBz (∼24%) might have caused nearly the same and equal average storm/activity intensity reductions in all latitudes (∼25%), though the irregular nature of the AE index makes the reduction very small (4%) at high latitudes, and small (∼11%) at mid latitudes mainly due to the small (0–9) quasi logarithmic scale of the Kp index. Plain Language Summary: The solar cycle 24 (SC24, 2010–2019) was the weakest solar cycle in 100 years with the activity being 1/3rd less compared to the previous solar cycle 23 (SC23, 1996–2009). Some good studies of the geomagnetic storms in SC24 have been reported, though a clear picture of the average storm/activity intensity at different latitudes is missing. We present the double superposed epoch analysis (DSEA) of the 135 and 61 ICME (interplanetary coronal mass ejection) driven clear geomagnetic storms/activities (DstMin ≤ −50 nT) identified in SC23 and SC24, respectively, at low, mid and high latitudes using the Dst, SymH, Kp and AE indices. The DSEA of the corresponding solar wind velocity V, IMF Bz and the product VBz is also presented. The results reveal that the average reduction in the main driver ‐VBz (∼24%) might have caused nearly the same and equal average storm/activity intensity reductions in all latitudes (∼25%), though the irregular nature of the AE index makes the reduction very small (4%) at high latitudes, and the 3‐hr resolution and small (0–9) quasi logarithmic scale of the Kp index makes the reduction small (11%) at mid latitudes. Key Points: Compared to SC23, the epoch average storm intensity in SC24 has much larger reduction in low latitudes than in mid and high latitudes The weakness of Kp and irregular variation of AE lead to small reduction in the average storm intensity in mid and high latitudes The combination ‐VBz seems to be the main solar wind driver determining the storm intensity in all latitudes